Bioethanol Production from Cassava Peel Treated with Sulfonated Carbon Catalyzed Hydrolysis - Primata Mardina; Chairul Irawan; Meilana Dharma Putra; Sylvera Bella Priscilla; Misnawati Misnawati; Iryanti Fatyasari Nata (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
A large amount of Cassava peel as biomass waste is generated by agricultural activities, and it led to a new pursuit to exploit the utilization of biomass waste. This research aimed to study the potential of Cassava peel as raw material for bioethanol production. This study was performed in 2 main processes, acid hydrolysis, and fermentation. The experiment was initiated by conducting acid hydrolysis (100°C and 60 min) on Cassava peel’s starch using sulfonated carbon catalyst palm oil empty fruit bunch (5%-w/v) to produce 13.53 g/L glucose. The glucose contained hydrolysates then continued to ferment at 30°C. The effect of fermentation time (h), pH, and shaking rate (rpm) of cassava peel’s starch fermentation using Saccharomyces cerevisiae was analyzed. The best result was found at pH 4.5 and 50 rpm for a 24 h reaction with 3.75 g/L of bioethanol concentration. This study revealed that Cassava peel is a promising feedstock for biofuel production.